A study of the financial statements and disclosures of Turkish special finance houses with reference to accounting standards for islamic banks and financial institutions - Hasibuan, Diaz (My University, 1998)
unknown
Keywords: Finans kurumları; Mali raporlar; Mali tablolar; Muhasebe; Yönetim ve yardımcı hizmetler